Pengaruh Sosiologis Komunitas Lesbian Gay Biseksual Dan Transgender Ditinjau Dalam Etika Kristen - Ekker Saogo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2021)
The Lesbian, Gay, Bisexual, and Transgender (LGBT) in the past was something deviant, but nowadays it has become a trend that is even considered natural by many people. This of course has a sociological impact. There is a view that says that the behavior of LGBT people is a biological natural behavior, so it needs to be accepted as something that cannot be changed. Some theories agree that LGBT behavior is influenced by environmental, parenting, and economic factors so that there are pros and cons for LGBT people. This study aims to see the sociological influence of the LGBT community by using a literature review. The results of the study show that LGBT is contrary to the truth of God's creation, namely the clear separation of sex, namely male and female. Also, this is contrary to the design of marriage that God built, namely heterosexuality and monogamy.